Klimageld: wichtig, aber kein Allheilmittel - Sara Holzmann (Wirtschaftsdienst, 2024)
– With the rise in the carbon price since the beginning of the year, the carbon dividend is once again a hot topic. Hopes are high that an imminent carbon dividend will ensure social equity and create more public support for climate policy. But are these expectations realistic or is this instrument and its effects exaggerated? This article calls for some expectation management when it comes to the carbon dividend, because as important as it is, socially just climate protection is much more than just mitigating rising carbon prices.
Keywords: Q52; Q58; H23; 330; Klimapolitik; Deutschland; Klimapolitik; Deutschland